Pupae transplantation to boost early colony growth in the weaver ant Oecophylla longinoda Latreille (Hymenoptera: Formicidae) - Ouagoussounon, I.; Sinzogan, A.A.C.; Offenberg, J.; Adandonon, A.; Vayssières, Jean-François; Kossou, D. (Universidade Estadual de Feira de Santana, 2013)
Oecophylla ants are currently used for biological control in fruit plantations in Australia, Asia and Africa and for protein production in Asia. To further improve the technology and implement it on a large scale, effective and fast production of live colonies is de¬sirable. Early colony development may be artificially boosted via the use of multiple queens (pleometrosis) and/or by adoption of foreign pupae in developing colonies. In the present experiments, we tested if multiple queens and transplantation of pupae could boost growth in young Oecophylla longinoda colonies. We found out that colonies with two queens artificially placed in the same nest, all perished due to queen fighting, suggesting that pleometrosis is not used by O. longinoda in Benin. In contrast, pupae transplantation resulted in highly increased growth rates, as pupae were readily adopted by the queens and showed high survival rates (mean = 92%). Within the 50-day experi¬ment the total number of individuals in colonies with 50 and 100 pupae transplanted, increased with 169 and 387%, respectively, compared to colonies receiving no pupae. This increase was both due to the individuals added in the form of pupae but also due to an increased per capita brood production by the resident queen, triggered by the adopted pupae. Thus pupae transplantation may be used to shorten the time it takes to produce weaver ant colonies in ant nurseries, and may in this way facilitate the imple-mentation of weaver ant biocontrol in West Africa.